Human Capital Agility: Reskilling and Up-skilling for the Future of Work - Sthapit, Arhan; Vaidya, Rashesh (Journal of Business and Social Sciences Research, 2025)
The future of work is undergoing profound transformation driven by technological acceleration, demographic shifts, climate imperatives, and evolving employment relationships. This editorial foregrounds human capital agility -the ability of individuals and organisations to adapt through reskilling and up-skilling -as the defining imperative for sustainable human resource strategies. Traditional human resource development (HRD) models, focused on static role-based training, are increasingly misaligned with labour markets characterised by skill obsolescence and emergent occupational forms. Agile HRD requires a decisive shift towards skills-based, capability-driven frameworks that integrate technological fluency with human-centric competencies. Drawing on recent global insights and South Asian scholarship, this write-up highlights the strategic necessity of reskilling and up-skilling, the enabling role of digital technologies, the importance of institutional collaboration, and the fertile ground for interdisciplinary research.